2014
DOI: 10.1095/biolreprod.113.113928
|View full text |Cite
|
Sign up to set email alerts
|

RNA-Seq Transcriptome Profiling of Equine Inner Cell Mass and Trophectoderm1

Abstract: Formation of the inner cell mass (ICM) and trophectoderm (TE) marks the first differentiation event in mammalian development. These two cell types have completely divergent fates for the remainder of the developmental process. The molecular mechanisms that regulate ICM and TE formation are poorly characterized in horses. The objective of this study was to establish the transcriptome profiles of ICM and TE cells from horse blastocysts using RNA sequencing (RNA-seq). A total of 12 270 genes were found to be expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
72
2
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(80 citation statements)
references
References 29 publications
3
72
2
3
Order By: Relevance
“…The newly reported transcripts were connected to overall biological processes like transcription. In general, the obtained results correspond to those commonly reported in other species (Iqbal et al 2014). However, it is noteworthy that the authors confirmed the possibility of identifying the sex of an embryo by comparing the levels of XIST (X inactive specific transcript, non-coding protein) previously reported in bovine embryos (Chitwood et al 2013).…”
Section: Gene Expression Profiling and Annotation Of Novel Genes In Tsupporting
confidence: 87%
See 2 more Smart Citations
“…The newly reported transcripts were connected to overall biological processes like transcription. In general, the obtained results correspond to those commonly reported in other species (Iqbal et al 2014). However, it is noteworthy that the authors confirmed the possibility of identifying the sex of an embryo by comparing the levels of XIST (X inactive specific transcript, non-coding protein) previously reported in bovine embryos (Chitwood et al 2013).…”
Section: Gene Expression Profiling and Annotation Of Novel Genes In Tsupporting
confidence: 87%
“…The obtained results have shown higher expression of genes coding blastocyst mucin (MUC1, MUC20), key enzymes catalyzing sialic acid biosynthesis (NAGK, NANS, CMAS, GNE), enzymes responsible for GalNAc metabolism (B3GNT2, B3GALNT1, ST3GAL4, GLT8D1), UDP-galactose transporters (SLC35A2, SLC35A3, SLC35A4), and genes involved in the synthesis of proteoglycan (GLANT gene family). The higher transcript abundance was also observed for genes coding enzymes involved in the biosynthesis of sulfated sugars genes, such as carbohydrate sulfotransferases (CHST), heparan sulfotransferases (HS2ST1), and transglutaminases (TGM3) (Iqbal et al 2014). The identification of gene expression patterns involved in blastocyst formation will broaden the existing knowledge and provide a foundation for further studies of mammalian embryology.…”
Section: Gene Expression Profiling and Annotation Of Novel Genes In Tmentioning
confidence: 96%
See 1 more Smart Citation
“…30,31 Briefly, 3-4 groups of 10 in vitro matured oocytes and in vitro produced embryos were used per stage of development. In a group of embryos, α-amanitin was added at the zygote stage at 50 μg/ ml and 8-cell embryos collected 56 h post fertilization.…”
Section: Rna-seq Datamentioning
confidence: 99%
“…A subsequent study focused on characterizing gene expression by RNA‐Seq in immunologically active tissues 95. Investigators have used RNA‐Seq to characterize the expression profile of genes critical to the differentiation and regulation of cells during embryogenesis,90 and to characterize the expression and inferred function of RNAs in the equine sperm transcriptome 89. Several studies also have used RNA‐Seq in horses to identify differentially expressed genes when comparing blood, muscle (obtained by biopsy), or both before and after exercise or racing 86, 87, 92.…”
Section: Next Generation Sequencing Techniquesmentioning
confidence: 99%